Perancangan Interior Akademi Sepak Bola di Malang dengan Konsep “Beginning Team” - Gautama Naritan; Cok Gede Padmanaba; Diana Thamrin (Intra, 2017)
Football is one of the most popular sports in Indonesia. In reverse, Indonesian football is slumped by lack of achievement both domestically and internationally. Indonesia has many talented young players. But not many soccer academies in Indonesia are able to develop these young players. Therefore, adequate facilities are needed that can support the development of young players talent.This design uses the method of collecting quantitative and qualitative data. The design method used is 3 stages, inspiration, ideation, and implementation. Academy soccer in Malang will be more emphasis on facilities that support the activities of students while in the academy. The main facilities are academic learning facilities, and soccer practice facilities. Other supporting facilities are public facilities and administrators. The design of this football academy will provide soccer practice and learning facilities for young Indonesian players.